Central autonomic regulation assessed by pupillary light reflex is impaired in children with attention deficit hyperactivity disorder - Hamrakova, A; Ondrejka, I; Sekaninova, N; Bona Olexova, L; Visnovcova, Z; Cesnekova, D; Hrtanek, I; Oppa, M; Hutka, P; Tonhajzerova, I (Physiological research, 2020)
It is assumed that the Attention Deficit Hyperactivity Disorder is associated with the central autonomic dysregulation, however, the studies are rare. Analysis of pupillary light reflex represents a non-invasive tool to provide information related to the central autonomic regulation; thus, we aimed to evaluate potential disturbances in the central autonomic integrity using pupillary light reflex examination in Attention Deficit Hyperactivity Disorder. We have examined 20 children with Attention Deficit Hyperactivity Disorder (10 boys, 13.0+/-2.3 years) and 20 age/gender-matched healthy subjects. Pupillary light reflex was examined at rest for both eyes using Pupillometer PLR-2000 (NeurOptics, USA). Evaluated parameters were: diameter of the pupil before the application of light stimulus and after illumination at the peak of the constriction, the percentual change of the pupil diameter during constriction, average constriction velocity, maximum constriction velocity and average dilation velocity. We found significantly lower percentual change of the pupil diameter during constriction for both eyes in Attention Deficit Hyperactivity Disorder group compared to controls (right eye: -25.81+/-1.23 % vs. -30.32+/-1.31 %, p<0.05, left eye: -25.44+/-1.65 % vs. -30.35+/-0.98 %, p<0.05). The average constriction velocity and maximum constriction velocity were significantly shortened in left eye in Attention Deficit Hyperactivity Disorder group compared to controls (p<0.05). Our findings revealed altered pupillary light reflex indicating abnormal centrally-mediated autonomic regulation characterized by parasympathetic underactivity associated with relative sympathetic predominance in children suffering from Attention Deficit Hyperactivity Disorder.
Keywords: hyperkinetická porucha; autonomní nervový systém; Photic Stimulation; světelná stimulace; Female; Reflex, Pupillary; Attention Deficit Disorder with Hyperactivity; Humans; ženské pohlaví; mladiství; mužské pohlaví; Autonomic Nervous System; lidé; Case-Control Studies; Male; reflex pupilární; Adolescent; studie případů a kontrol